Mapping CRISPR research, innovation, and diffusion activities in agriculture: Cross-national - Samantha Zyontz (Expertenkommission Forschung und Innovation (EFI), 2024)
This report updates and expands the paper, patent, and company datasets collected for Zyontz and Pomeroy-Carter (2021) through 2022. Particular attention is paid to worldwide CRISPR activity in plant applications. The results from the databases updated for this report reveal a number of important trends in the global CRISPR plant ecosystem. First, China dominates in CRISPR plants, but there are many countries that innovate in this space, including the United States and European Union. Second, innovation strategies in CRISPR plants are still influenced by the existing academic, business, and cultural environments at the time CRISPR was introduced. Third, Germany produces very high quality scholarship in CRISPR plants and has a number of well-established companies that patent, but there is little evidence of university-company co-creation that helps to translate ideas into products and create new ventures.
Keywords: 330